(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In this article, the transition to a green economy in order to ensure the stability of the economy, prevention of climate change, inclusive economic growth, the use of budget and fiscal policy tools to achieve environmental goals and the transition to green budgeting practice in Uzbekistan, the advantages of green budgeting, and the issues that exist during the transition to this practice are highlighted. Given.